Controlled synthesis of manganese oxyhydroxide nanotubes : implications for high-efficiency supercapacitors - Shi, Wenhui (2014)
Successful attempts have been made to control the synthesis of tubular MnOOH with nanodimensions on high electronic conductivity graphite felt (GF) to be used as a flexible supercapacitor electrode. As a fundamental study, the time-dependent kinetics was investigated to interpret its formation mechanism, which can be depicted as the curling of a two-dimensional precursor into a one-dimensional structure with a hollow interior. As a result of the nanotube structure, the active surface area of MnOOH is completely accessible to electrolyte ions and has a shorter charge-transport length and greater ability to withstand structural deformation. Hence, hollow-structured MnOOH shows great promise as an electrochemical system, which is reflected in its high specific capacitance of 1156 F g−1 at 1 A g−1. Furthermore, the high energy density of 1125 W h kg−1 and power density of 5.05 kW kg−1 reveal the outstanding energy-storage behavior of the MnOOH/GF composites as flexible supercapacitor electrodes.